1999
DOI: 10.3109/10428199909093721
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Receptors and the Differentiation of Human Megakaryocytes in vitro

Abstract: We investigated the expression and functions of extracellular matrix receptors (or integrins) in the course of the differentiation of human megakaryocytes (Mks) leading to the formation of platelets. Integrins beta1 or Very Late Antigens (VLA) are specialized transmembrane receptors allowing the attachment of the cells to collagen (VLA-2), fibronectin (VLA-4 and -5) and laminin (VLA-6). A proportion of committed megakaryocytic progenitor cells (CFU-MK) adhere to fibronectin but not to collagen or laminin. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…[43] The LBL deposition of nano-structured clay platelet and PDDA increased nano-scale roughness and created surface charge and stiff film, which worked in concert, along with adhered proteins, to bind and stimulate cells. We knew from the literature that megakaryocytes and CFU-MK bind to fibronectin and that TPO promotes early hematopoietic cell and megakaryocyte adherence to fibronectin [44]. We found that with the combination of both TPO and fibronectin, utilizing the SRC kinase inhibitor medium, platelet production lasted longer at a higher level vs. only one or the other or neither.…”
Section: Discussionmentioning
confidence: 97%
“…[43] The LBL deposition of nano-structured clay platelet and PDDA increased nano-scale roughness and created surface charge and stiff film, which worked in concert, along with adhered proteins, to bind and stimulate cells. We knew from the literature that megakaryocytes and CFU-MK bind to fibronectin and that TPO promotes early hematopoietic cell and megakaryocyte adherence to fibronectin [44]. We found that with the combination of both TPO and fibronectin, utilizing the SRC kinase inhibitor medium, platelet production lasted longer at a higher level vs. only one or the other or neither.…”
Section: Discussionmentioning
confidence: 97%
“…38 GPIba and PECAM are later megakaryocytic markers and may contribute to growth arrest and proplatelet formation, respectively. 38,44,45 ABO antigens are also expressed by a4b1 and a5b1 integrins, where they are known to directly influence integrin function. In epithelial tumors, loss of A/B antigens, with a concomitant increase in H and Le Y , is associated with increased fibronectin binding, cell adhesion, cell motility, and resistance to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In epithelial tumors, loss of A/B antigens, with a concomitant increase in H and Le Y , is associated with increased fibronectin binding, cell adhesion, cell motility, and resistance to apoptosis. [46][47][48] In marrow, integrins mediate CD34+ PBPCs and megakaryocyte adhesion to ECM and stromal fibroblasts, 40,45,49 inhibiting apoptosis, 50 while promoting fibroblast growth, megakaryocyte differentiation, and proplatelet formation. 18,39,45 Finally, ABO might influence the binding and cellular response to required growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…MKs express two main receptors for collagen, integrin-α2β1 and glycoprotein VI [47]; however, MK expression of leukocyte-associated immunoglobulin-like 1 (LAIR1) and discoidin domain receptor (DDR1) that also bind collagen have been described in the literature [48,49]. Early MK progenitors (CFU-MK) have a lower affinity for adhering to collagen compared to later MK progenitors [50], which is interesting as integrin-α2β1 and glycoprotein VI expression occurs early in MK development [50,51]. It has been established that collagen I inhibits proplatelet formation (PPF) in order to prevent the release of immature platelets in the bone marrow, while collagen IV and laminin support PPF in the sinusoids [52].…”
Section: Integrins As Ecm Sensors In the Context Of Megakaryocytosismentioning
confidence: 99%
“…HSPC cultures on fibronectin resulted in an increase in mouse HSC with an increase in MK output [13]. The major fibronectin binding integrins on MKs are VLA-4 (α4β1) and VLA-5 (α5β1), which are expressed throughout MK development [50,60]. HSC cultures produced more CFU-MKs on fibronectin as stiffness increased [8].…”
Section: Integrins As Ecm Sensors In the Context Of Megakaryocytosismentioning
confidence: 99%